2011
DOI: 10.17224/energagric.2011v26n3p80-97
|View full text |Cite
|
Sign up to set email alerts
|

Remoção Pela Chuva De Diferentes Formulações De Flutriafol Aplicadas Em Soja, Com E Sem a Adição De Óleo Mineral Na Calda

Abstract: RESUMO:O presente trabalho teve por objetivos verificar o efeito da remoção pela chuva de diferentes formulações de flutriafol, em condições de laboratório, aplicadas em plantas de soja com e sem a adição de óleo na calda de pulverização, assim como verificar a influencia da presença do óleo na calda quanto ao espectro de gotas. O experimento considerou dez caldas resultantes da interação de cinco tratamentos contendo o flutriafol (quatro formulações de flutriafol isolado e uma mistura de flutriafol com tebuco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Even 3 hours after application of the fungicide, there was still a reduction in the amount of active ingredient in the leaflets. In an experiment conducted by Oliveira (17), the values observed 1, 2 and 48 hours after application did not reflect the common sense of the fungicide market, which recommends a minimum interval of 2 hours between application and rainfall.…”
Section: Resultsmentioning
confidence: 90%
“…Even 3 hours after application of the fungicide, there was still a reduction in the amount of active ingredient in the leaflets. In an experiment conducted by Oliveira (17), the values observed 1, 2 and 48 hours after application did not reflect the common sense of the fungicide market, which recommends a minimum interval of 2 hours between application and rainfall.…”
Section: Resultsmentioning
confidence: 90%
“…These results indicate that longer periods between application and precipitation lead to increased chances of drying and adherence of the deposits to the treated leaf surface, or to higher penetration or translocation of the product through the plant (BRUGGEN et al, 1987;SCHEPERS, 1996;DUARTE, 2008;OLIVEIRA, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Santos et al (2002) observed that exposure to 20 mm of simulated rainfall, 15 min after each application, did not interfere with the efficacy of cyproconazole and tetraconazole in the control of coffee leaf rust. However, it is well known that shorter duration between pulverization and exposure to rain increase the chance of fungicides being washed off (OLIVEIRA, 2009).…”
Section: Introductionmentioning
confidence: 99%